2023
DOI: 10.1101/2023.10.02.560486
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiple independent acquisitions of ACE2 usage in MERS-related coronaviruses

Cheng-Bao Ma,
Chen Liu,
Young-Jun Park
et al.

Abstract: The unknown identity of the entry receptors utilized by many coronaviruses has significantly impeded our comprehensive understanding of these important pathogens. We recently reported an unexpected usage of angiotensin-converting enzyme 2 (ACE2), instead of Dipeptidyl peptidase-4 (DPP4), for cellular entry by NeoCoV and PDF-2180, close relatives of MERS-CoV that infect African bats. However, the presence and distribution of other ACE2-using merbecoviruses remain enigmatic. In this study, through sequence and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 107 publications
0
3
0
Order By: Relevance
“…According to the tree topology, we classified merbecoviruses into 9 groups (Fig. 1 ): the MERS-CoV group that is a known human DPP4 (hDPP4)-using virus that infects camels and humans [ 15 ]; the group 1 bat MERS-related CoVs (MCr-CoVs) consisting of NeoCoV and PDF-2180 which were described to use bat ACE2 (bACE2) orthologues, and less efficiently human ACE2 (hACE2) [ 16 ]; the group 2 bat MCr-CoVs that includes the PnNL2018B and MOW15-22 that were recently documented to also use bACE2 [ 17 ]; the group 3 bat MCr-CoVs which includes bat viruses, like BtCoV-422 that can use hDPP4 and bDPP4 [ 46 ], and HKU25 that can use hDPP4 [ 47 ]; the group 4 bat MCr-CoVs that includes PaGB01 that cannot use hACE2, hDPP4 and human aminopeptidase N (hAPN) [ 48 ]; the Tylonycteris HKU4 group that uses hDPP4 and bDPP4 [ 49 , 50 ]; the recently identified pangolin HKU4 that efficiently uses hDPP4, bDPP4, and pangolin DPP4 [ 51 ]; the Pipistrellus HKU5 group that cannot use hACE2, bACE2, hDPP4 or bDPP4 [ 16 , 46 , 49 ], but was recently shown to use Pipistrellus abramus ACE2 (the group’s reservoir bat host) [ 52 ], and lastly, the Hedgehog-CoV-1 group which also cannot use hACE2 or hedgehog ACE2 as its viral receptor [ 16 ]. The latter is the outgroup of the known merbecoviruses based on rooting by the sarbecoviruses (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the tree topology, we classified merbecoviruses into 9 groups (Fig. 1 ): the MERS-CoV group that is a known human DPP4 (hDPP4)-using virus that infects camels and humans [ 15 ]; the group 1 bat MERS-related CoVs (MCr-CoVs) consisting of NeoCoV and PDF-2180 which were described to use bat ACE2 (bACE2) orthologues, and less efficiently human ACE2 (hACE2) [ 16 ]; the group 2 bat MCr-CoVs that includes the PnNL2018B and MOW15-22 that were recently documented to also use bACE2 [ 17 ]; the group 3 bat MCr-CoVs which includes bat viruses, like BtCoV-422 that can use hDPP4 and bDPP4 [ 46 ], and HKU25 that can use hDPP4 [ 47 ]; the group 4 bat MCr-CoVs that includes PaGB01 that cannot use hACE2, hDPP4 and human aminopeptidase N (hAPN) [ 48 ]; the Tylonycteris HKU4 group that uses hDPP4 and bDPP4 [ 49 , 50 ]; the recently identified pangolin HKU4 that efficiently uses hDPP4, bDPP4, and pangolin DPP4 [ 51 ]; the Pipistrellus HKU5 group that cannot use hACE2, bACE2, hDPP4 or bDPP4 [ 16 , 46 , 49 ], but was recently shown to use Pipistrellus abramus ACE2 (the group’s reservoir bat host) [ 52 ], and lastly, the Hedgehog-CoV-1 group which also cannot use hACE2 or hedgehog ACE2 as its viral receptor [ 16 ]. The latter is the outgroup of the known merbecoviruses based on rooting by the sarbecoviruses (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, although MERS-CoV utilizes dipeptidyl peptidase 4 (DPP4) as the viral receptor [ 15 ], a previous study by Xiong et al (2022) showed that NeoCoV and PDF-2180 utilize angiotensin-converting enzyme 2 (ACE2) as their viral receptor [ 16 ]. Additionally, another study has identified bat coronaviruses related to MERS-CoV that also use ACE2 as their viral receptor [ 17 ]. These findings suggest that receptor usage of these coronaviruses switched from ACE2 to DPP4 (or from DPP4 to ACE2) during their recent evolution.…”
Section: Introductionmentioning
confidence: 99%
“…While MERS-CoV uses the receptor dipeptidyl peptidase IV (DPP4) to infect cells, several studies have shown that some bat merbecoviruses do not use DPP4 and instead use angiotensin converting enzyme 2 (ACE2) to infect their hosts [21][22][23] .…”
Section: Introductionmentioning
confidence: 99%